2019
DOI: 10.3390/ijerph16224394
|View full text |Cite
|
Sign up to set email alerts
|

Use of Meditation and Cognitive Behavioral Therapies for the Treatment of Stress, Depression and Anxiety in Students. A Systematic Review and Meta-Analysis

Abstract: The prevalence of mental health problems within students due to high academic demands and learning difficulties is a current challenge the field of education. The aim of this study is to review the scientific literature in order to analyze the effect produced by cognitive-behavioral programs and meditation strategies on stress, anxiety, and depression in students. A further aim is to identify the determinants of treatment success. The bibliographic search was carried out using Web of Science, specifically in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 63 publications
(76 reference statements)
3
41
0
6
Order By: Relevance
“…In relation to the emotional regulation, MEL training seemed to reduce anxiety levels in the experimental group participants; this is an important result since anxiety could hinder learning and, consequently, the achievement of good academic results [5,6,[55][56][57][58]. As regard resilience, no significant effect was observed between the two groups post-test.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In relation to the emotional regulation, MEL training seemed to reduce anxiety levels in the experimental group participants; this is an important result since anxiety could hinder learning and, consequently, the achievement of good academic results [5,6,[55][56][57][58]. As regard resilience, no significant effect was observed between the two groups post-test.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous experimental studies have assessed the effectiveness of time-limited (typically 8 weeks) mindfulness-based training offered to university students [47][48][49]. The results have shown that mindfulness improves self-control abilities and awareness (e.g., [50]), increases self-efficacy (e.g., [25,51]), coping strategies (e.g., [52]), that are connected with resilience, enhances attentive skills (e.g., [53]), improves cognitive performance and metacognition (e.g., [54]), and decreases stress, anxiety, and depression (e.g., [47,[55][56][57][58]). As a consequence, it is not surprising that mindfulness-based training has been introduced permanently in several universities around the world [40,43,59,60].…”
Section: Mindfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings can provide some insights for further adaption of mindfulness exercises and teachings in mindfulness interventions provided to university students (for example, stressing that non-reacting is not indifference in students within the under-challenged subtype). Combining the identification of burnout subtypes and tailoring mindfulness contents and practices accordingly may increase the efficacy of mindfulness-based interventions in students, a population for which, to date, there is still much room for improvement [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“… 90 The suggestions presented in Tables 1 and 2 offer a structured approach for health care teams based on available evidence. 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125…”
Section: Implications Of Psychological Milieu For Critically Ill Patimentioning
confidence: 99%